Electroacupuncture for Decorticate Rigidity of the Upper Limbs in a Patient with Anoxic Brain Damage - WooSang Jung; SeungWon Kwon; SeongUk Park; SangKwan Moon; JungMi Park; ChangNam Ko; KiHo Cho (Case Reports in Medicine)
Decorticate rigidity is a type of abnormal posturing that can make it difficult to move a patient and to change the patient’s position to prevent a decubitus ulcer. This condition poses a latent risk of bed sores. To prevent those complications, we used electroacupuncutre for decorticate rigidity of the upper limbs in a patient with anoxic brain damage. A 51-year-old man complained of rigidity of both of the upper and lower extremities due to anoxic brain damage. His rigidity was exhibited as flexed arms and extended legs, which are the typical positions in decorticate rigidity. Prior to electroacupuncture, his decorticate rigidity was treated with dantrolene sodium and baclofen. However, his rigidity had not improved. This patient received total 41 sessions of electroacupuncture. The patient’s Modified Ashworth’s Scale changed from 4 at baseline to 2 after the treatment, indicating an improvement in the rigidity of the upper limbs. Preston’s Hypertonicity Scale and passive ROM of the elbow joints also improved. We report the observed effects of electroacupuncture for decorticate rigidity of the upper limbs in a patient with anoxic brain damage. Further controlled studies are needed to determine whether electroacupuncture is a useful alternative treatment for decorticate rigidity in patients with anoxic brain damage.